Cage kings : how an unlikely group of moguls, champions, and hustlers transformed the ufc into a 10 billion industry /: how an unlikely group of moguls, champions, and hustlers transformed the ufc into a 10 billion industry. (2023) - Thomsen, Michael
No abstract available